From Page to Screen: The Plot Transformation of Roald Dahl's Matilda into Matthew Warchus's Movie - Dina Dyah Kusumayanti; Ferina Windi Setiani; Yanuaresti Kusuma Wardhani (Journal of Language and Literature, 2025)
This article discusses the adaptation of Roald Dahl's novel Matilda (1988)into the movie Roald Dahl's Matilda The Musical (2022), directed by Matthew Warchus. This research focuses on the transformation of intrinsic elements, which is the plot of the novel to the movie. The transformation of the novel into the movie is classified as the telling-to-showing mode. The transformation from written text to audio-visual media involves changes such as subtractions and additions, which are influenced by the differences in the mediums of expression. The three main issues discussed in this article are (1) the transformations of the plot in the novel into the movie, (2) the ideology reflected in the works by the author and the adapter, and (3) the motives of the adapter. This research uses a comparative method with Linda Hutcheon's Theory of Adaptation and Roland Barthes's semiotics. The findings show the ideology of patriarchy by the author in the novel and the ideologies of children's education rights and feminism by the adapter in the movie. Furthermore, this study reveals the motives of the adapter, which include personal motives, as reflected in the ideological changes, and economic lure motives, demonstrating how creative and commercial factors shape the adaptation process.